Revisiting the Regular Education Initiative: Multi-tiered Systems of Support Can Strengthen the Connection Between General and Special Education - Leach, Debra; Helf, Shawnna (Journal of the American Academy of Special Education Professionals, 2016)
In 1986 Madeleine Will proposed the Regular Education Initiative (REI) to share possibilities for eliminating the divide between general and special education. Although great strides have been made over the past several decades in regard to the inclusion of students with disabilities, a significant divide between general and special education still exists. The purpose of this article is to discuss how multi-tiered systems of support (MTSS) models for implementing evidence-based instruction to students with and without disabilities are used to create a culture of inclusive practices that encourage collaboration between general and special education. We offer suggestions for schools looking to establish and/or strengthen a model that is both cohesive and integrated.